1244 The TAL Suction Retractor: A Simple Technique for Visualising the Transverse Acetabular Ligament (TAL) During Total Hip Replacement (THR) Surgery. (12th October 2021) - Murphy, B; Pollock, R; Ramchurn, S; Hurson, C
Abstract: Introduction: The transverse acetabular ligament (TAL) is an anatomical landmark that is of particular use during primary total hip replacements (THR). Visualisation is important to aid the orientation of the acetabular cup and it is a structure that can be identified in virtually every primary hip replacement surgery. We introduce a simple technique to facilitate this. Method: A thoracic suction catheter is taped to the distal end of a blunt Hohmann's retractor with two steristrips wrapping around the catheter and retractor leaving approximately 1-1.5cm of retractor exposed. Our preference is for a thoracic suction catheter with side holes and a proximal end which allows direct connection with the tip of the Yankauer suction. The blunt Hohmann's retractor is used as the inferior acetabular retractor in the usual way, placed inferior to the transverse acetabular ligament, resting on the posterior ischial surface. The catheter suction tip should lie just under the TAL, in the most dependant point of the wound. Results: The TAL suction catheter can be used continuously or intermittently to facilitate visualisation of the TAL during reaming, trialling, and acetabular cup placement. The TAL suction retractor provides suction in the most dependant point of the surgical wound, preventing unnecessary movement and facilitates a clutter-free surgical field leading to more streamlined and efficient surgery with potential reduced operative times. Conclusions: The transverse acetabular ligament (TAL) suction retractor is a simple improvised surgical tool that makes it easier to visualise the TAL during acetabular preparation in total hip replacements.